O controle público dos incentivos fiscais para a tutela da igualdade tributária - Silva, Roberto Camargo da (2012)
Equality is a fundamental right threatened by the obscurity of relations, especially regarding subjects, objects, requirements and principally by the consequences of the acts committed. Only adequate publicity allows the reactions to offenses or threats to equality. Without information there is no possible control. Without control, a suspicion arises as to whether the relationship is respecting the equal treatment of the parties and interested third parties. In the case of legal relations, public control is essential for the validation begore the regulatory system that oversees equality. Substantive equality depends on information made available to the widest possible audience, at the right time and in a clear, accurate and structured form. This perspective should be the widest possible in legal relationships that have the participation of the State since the constituted powers in the three spheres of government have a constitutional duty to preserve and promote the equal treatment of citizens. Under tax law, particularly in relation to tax incentives, arisen threats to equality must be inhibited via public control not only by relief legislation that will be edited, which necessarily must comply with the formal requirements and materials provided constitutionally, but even effects of derivatives, since inequalities may arise in time after the entry into force of regulatory standards. In the Brazilian reality these threats to equal taxation in granting tax incentives are derived from the transparency deficit caused by insufficient objective references that can orientate public control, which compromises the effectiveness of their normative acts. To assist in overcoming this deficiency this work aims to provide objective parameters that besides qualifying the exercise of citizenship, can serve as support for the definition of public relief policies and for the official control legally referred to the meeting of the effectiveness of constitutional norms that safeguard equality.